2016
DOI: 10.1152/ajplung.00312.2015
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent phospholipase A2modulates infection-induced diaphragm dysfunction

Abstract: Supinski GS, Alimov AP, Wang L, Song X, Callahan LA. Calciumdependent phospholipase A 2 modulates infection-induced diaphragm dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Consistent with existing knowledge [ 1 , 2 , 30 32 ], our study found that sepsis with following CMV could make significant diaphragm injury in rat model. Moreover, since diaphragm contractile properties improvement with MgSO 4 administration after CLP was recorded in our study, we, therefore, assume the MgSO 4 therapeutic potential for sepsis-induced diaphragmatic dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with existing knowledge [ 1 , 2 , 30 32 ], our study found that sepsis with following CMV could make significant diaphragm injury in rat model. Moreover, since diaphragm contractile properties improvement with MgSO 4 administration after CLP was recorded in our study, we, therefore, assume the MgSO 4 therapeutic potential for sepsis-induced diaphragmatic dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Nonencapsulated heme is an important injurious agent in several pathologies such as the endothelial injury after lipopolysaccharide exposure (26), lung injury after Libby amphibole asbestos exposure (27), hyperoxia-induced lung injury (28), pulmonary hypertension in sickle cell anemia (29), and trauma-hemorrhage (30). Nonencapsulated heme causes oxidative stress by generating reactive species and redox-active iron capable of initiating lipid peroxidation (31,32). It intercalates into cell membranes and causes oxidative loss of plasma membrane integrity (33).…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiological mechanisms of DW are usually classified as infection/inflammation-related or ventilator-induced mechanisms 33, 34 . Infection causes cytokine release, which in turn induces mitochondrial free radical production 35, 36 , contributing to the reduction in muscle endurance and strength 36 . Histopathological findings include injury of the muscle fibers with disrupted sarcomeres 37, 38 .…”
Section: Diaphragmatic Weakness and Icu-aw: Different Clinical Entitimentioning
confidence: 99%